A review of important considerations in the compression molding process of short natural fiber composites - Jaafar, Jamiluddin; Siregar, Januar Parlaungan; Tezara, Cionita; Mohamad Hamdan, Mohammad Hazim; Rihayat, Teuku (Springer Nature, 2019)
The study reviewed crucial parameters in the compression molding process for biocomposites affecting the properties of short natural fiber-reinforced polymer composites. The evaluation of drying and compounding processes between the polymer and short natural fiber was an essential consideration before the compression molding of biocomposites. Meanwhile, the parameters of molding temperature, compression pressure, and duration appeared to be other crucial and significant considerations requiring attention. In this study, all significant considerations affecting the performance of biocomposites were highlighted to provide essential information in the compression molding process of natural fiber composites topic. The findings from the present study are expected to improve the performance of short natural fiber-reinforced polymer composites and be an alternative to conventional polymer in various engineering applications in the future.